Corrosion-resistant rolled composite steel plate and manufacturing method thereof
By forming a stable MC precipitation phase in the carbon steel substrate and fixing the carbon element, the problem of degradation of corrosion resistance of stainless steel caused by carbon element diffusion is solved, and the high-temperature corrosion resistance and safety performance of the rolled composite steel plate is improved.
Patent Information
- Application Number
- CN202311425041.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-31
AI Technical Summary
When existing rolled composite steel plates are in service for a long time at high temperatures, the carbon elements in the carbon steel substrate diffuse to the composite stainless steel through the transition layer, resulting in a decrease in the corrosion resistance of the stainless steel and a safety hazard.
By forming a large number of fine diffusion distributions and stable high-temperature performance in the carbon steel substrate, free carbon elements in the fixed steel are prevented from diffusing to the interface of the composite steel plate.
It effectively reduces the carbide precipitation in composite stainless steel, and improves the corrosion resistance and safety performance of rolled composite steel plates under high temperature conditions.
Smart Images

Figure BDA0004521950730000191 
Figure BDA0004521950730000201 
Figure BDA0004521950730000211
Abstract
Description
Technical Field
[0001] The invention relates to corrosion-resistant steel and a manufacturing method thereof, in particular to a corrosion-resistant rolled composite steel plate and a manufacturing method thereof, which is suitable for equipment in the working temperature range of room temperature to 300°C in energy industries such as electric power and chemical industry. Background Art
[0002] Composite steel plates made of low alloy steel + various corrosion-resistant materials are often used in crude oil processing, energy and chemical industries because of their high mechanical strength and strong corrosion resistance. With the rapid development of the national economy, there is an increasing demand for various energy-related raw materials such as oil and fertilizers. In order to improve energy production efficiency, it is imperative to make energy production and processing equipment large-scale, high-parameter (higher temperature, higher pressure) and lightweight. This equipment upgrade demand puts higher requirements on the performance of steel plates for manufacturing equipment, that is, it requires such steel plates to have not only higher strength and hardness, but also excellent toughness, processing and forming performance, and better corrosion resistance.
[0003] The production process of traditional composite steel plates is the explosive composite process. The main problem of this production process is that when using explosives for explosive composite, a large amount of harmful gases will be generated, which will have an adverse impact on the environment, that is, this type of production process does not meet environmental protection requirements; at the same time, the bonding rate at the interface of the explosive composite steel plate is low, and sometimes cannot meet the bonding rate requirement of more than 97%. When this type of steel plate is used to manufacture various high-temperature, high-pressure, and large-scale container equipment, there will be great safety hazards. Once the composite steel plate joint is separated and the equipment fails, it will have a huge impact on the safety of life and property.
[0004] Compared with explosive composite steel plates, the bonding rate of rolled composite steel plates is greatly improved to more than 99%, and the production process is more environmentally friendly than explosive composite steel plates. Therefore, in recent years, the production scale and engineering application of rolled composite steel plates have been expanding year by year.
[0005] However, whether it is explosive composite steel plate or rolled composite steel plate, a certain transition layer will be produced at the interface between carbon steel and other corrosion-resistant materials. Especially when the steel plate is in service for a long time at high temperature, the carbon element in the carbon steel substrate will diffuse to the composite stainless steel through the transition layer. Once a large amount of carbides are formed in the composite stainless steel, intergranular corrosion will occur, which will have an adverse effect on the corrosion resistance of the composite corrosion-resistant material, and eventually lead to the failure of the composite material, forming a safety hazard.
[0006] Therefore, how to reasonably design the alloy composition and production process of the carbon steel base layer to minimize the negative impact on the corrosion resistance of the corrosion-resistant material caused by the diffusion of carbon elements in the carbon steel material through the transition layer to the composite stainless steel under long-term high-temperature service has become an urgent requirement for improving the comprehensive performance and safety performance of rolled composite steel plates.
[0007] Prior art, such as: Chinese patent publication number CN107310218A discloses a composite bulletproof steel plate and a manufacturing method thereof, wherein the composite bulletproof steel plate comprises: a hard steel layer and a soft steel layer spaced apart from each other, wherein the surface layer of the composite bulletproof steel plate is a hard steel layer, and the hard steel layer and the soft steel layer are atomically bonded by rolling and compounding; wherein the chemical element mass percentage of the soft steel layer is: C: 0.001-0.01%, 0<Si≤0.005%, Mn: 0.05-0.15%, 0<Al≤0.005%, Ti: 0.01-0.10%, and the remainder is Fe and other inevitable impurities. The composite bulletproof steel plate has multiple layers of soft steel layers and hard steel layers. The hard steel layer cracks into small fragments when subjected to the impact of a projectile, consuming the impact energy, and at the same time, the soft steel layer changes the direction of the bullet and increases the forward resistance of the bullet, thereby having a better bulletproof effect. The core technical solution of the invention is to effectively consume the kinetic energy of the bullet by arranging a hard steel layer with higher strength and a soft steel layer with better toughness. However, the technical solution of the invention does not involve the transition interface between the hard steel layer and the soft steel layer, nor does it involve the diffusion of carbon elements in carbon steel materials into the composite material.
[0008] Chinese patent publication number CN107310219A discloses "a bulletproof steel plate with excellent cold bending processing performance and a manufacturing method thereof". The bulletproof steel plate with excellent cold bending processing performance in the patent comprises: three layers of soft steel layers and two layers of hard steel layers, wherein the three layers of soft steel layers and the two layers of hard steel layers are arranged at intervals from each other, and the surface layer of the bulletproof steel plate is a soft steel layer, and the hard steel layer and the soft steel layer are atomically bonded by rolling and compounding; wherein the mass percentage of chemical elements in the soft steel layer is: C: 0.001-0.01%, 0<Si≤0.005%, Mn: 0.05-0.15%, 0<Al≤0.005%, Ti: 0.01-0.10%, and the balance is Fe and other inevitable impurities. The hard steel layer changes the direction of the projectile, and the soft steel layer on the surface has excellent plasticity to ensure that it does not crack when stretched and deformed. When subjected to the impact of the projectile, it cracks into small fragments, consuming the impact energy. At the same time, the soft steel layer in the core changes the direction of the bullet and increases the resistance of the bullet, thus having a better bulletproof effect. This patent also uses the technical solution of arranging hard steel and soft steel at intervals to reduce the kinetic energy of the bullet. The technical solution does not involve the bonding interface of the rolled composite steel plate and the diffusion of elements.
[0009] Chinese patent publication number CN108231273A discloses a method for improving the interface of copper-aluminum composite materials, which includes the following steps: pre-coating or depositing graphene at the interface of copper and aluminum, and then processing and compounding copper, aluminum and graphene; the coating or deposition method is one of coating, electroplating, and chemical vapor deposition; the processing and compounding method is one of rolling compounding, extrusion compounding, and drawing compounding; the graphene is powder or film. Using the method of the present invention, adding graphene to the interface of copper and aluminum can ensure the interface bonding, while preventing the generation of brittle and poorly conductive intermetallic compounds at the interface, and improve the interface bonding and conductivity. This patent involves a method for improving the interface position of a composite material, but since the substrate and composite material of the composite material are copper and aluminum respectively, it has little reference significance for the composite rolling technology of carbon steel and stainless steel. The patent also does not mention the influence of element diffusion at the interface on material properties.
[0010] In summary of the above patents, in the existing rolled composite steel plate technology, there is little consideration for the transition layer at the interface between the base and the composite material, especially the influence of the elements in the base material through the transition layer on the performance of the composite stainless steel. Basically, no targeted measures have been taken to reduce the possibility of weakening the corrosion resistance of stainless steel due to the precipitation of carbides at the interface of the composite material. Especially in the chemical and energy industries, many times, the operating temperature of composite steel plate manufacturing equipment is at high temperature (within 300°C). If the equipment operates at high temperature for decades, the elements at the material interface may diffuse again, especially the carbon elements on the carbon steel side diffuse into the stainless steel composite layer, which will form more carbides, further reducing the corrosion resistance of stainless steel and forming potential accidents. Summary of the invention
[0011] The purpose of the present invention is to provide a corrosion-resistant rolled composite steel plate and a method for manufacturing the same, which can reduce the possibility of intergranular corrosion and failure of the stainless steel on the composite side by blocking or reducing the diffusion of carbon elements on the carbon steel side at the interface of the composite steel plate, thereby comprehensively improving the corrosion resistance and safety performance of the rolled composite steel plate under high temperature working conditions, and is suitable for equipment in the energy industries such as electric power and chemical industry with an operating temperature of room temperature to 300°C.
[0012] To achieve the above object, the technical solution of the present invention is:
[0013] A large number of finely dispersed MC (M represents one or more of Nb and Ti) precipitation phases with stable high-temperature performance are formed in the composite steel plate substrate of the present invention. These stable carbide precipitation phases can fix the free carbon element in the steel in the substrate carbon steel, thereby avoiding the diffusion and migration of the carbon element in the carbon steel to the interface of the rolled composite steel plate under high-temperature working conditions, resulting in an increase in the carbon element concentration in the stainless steel near the interface, and a large number of carbide precipitation phases are generated at the stainless steel grain boundaries, inducing intergranular corrosion, and ultimately weakening or even losing the anti-corrosion function of the composite material.
[0014] Specifically, the corrosion-resistant rolled composite steel plate of the present invention comprises a substrate, a composite layer and a transition layer between the substrate and the composite layer; wherein the weight percentage of the components of the substrate is: C: 0.01% to 0.10%, Si: 0.2% to 0.7%, Mn: 0.30% to 1.70%, Ti: 0.006% to 0.012%, Als: 0.008% to 0.018%, Nb: 0.0090% to 0.050%, B: 0.0010% to 0.0050%, N: 0.0015% to 0.0050%, P≤0.017%, S≤0.020%, O≤0.0050%, and the balance comprises Fe and other inevitable impurities;
[0015] The surface microstructure of the composite steel plate substrate is 60-80% ferrite + 20-40% pearlite + MC precipitation phase, and the central microstructure of the substrate is 30-40% pearlite + 60-70% ferrite + MC precipitation phase; wherein M represents one or two of Nb and Ti, the average major axis length of the MC precipitation phase is less than 600nm, and the volume density of the MC precipitation phase with a major axis length less than 600nm is greater than 2.0×10 4 Pieces / mm 3 ;
[0016] The composite steel plate is made of stainless steel, and its microstructure contains MC precipitated phase, wherein M represents one or more of Cr, Mo, Nb, and Ti, the average major axis length of the MC precipitated phase is less than 700 nm, and the volume density of the MC precipitated phase is less than 1.0×10 4 Pieces / mm 3 ; Preferably, the stainless steel is austenitic stainless steel, ferritic stainless steel, duplex stainless steel or super stainless steel.
[0017] Furthermore, in the composite steel plate base material components, the balance is Fe and other inevitable impurities.
[0018] Furthermore, the composite steel plate substrate composition also contains at least one of the following chemical elements: 0<Ca≤0.0055%, 0<Ni≤0.65%, 0<Cu≤0.55%.
[0019] Preferably, in the composite steel plate substrate, the number ratio of MC precipitates with a major axis length of less than 600 nm to all MC precipitates is greater than 50%.
[0020] Preferably, in the composite steel plate layer, the number ratio of MC precipitated phases with a major axis length of less than 700 nm to all MC precipitated phases is greater than 50%.
[0021] Furthermore, there is a very small amount of σ phase in the microstructure of the composite steel plate layer, and the proportion of the σ phase is ≤1.5%. Preferably, the proportion of the σ phase near the transition layer is ≤0.5%.
[0022] Preferably, the thickness of the composite steel plate substrate is ≥6 mm, the thickness of the composite layer is ≥2 mm, and preferably, the thickness of the transition layer is ≤230 μm.
[0023] The yield strength of the composite steel plate substrate of the present invention is ≥255MPa, the tensile strength is ≥390MPa, the cross-sectional shrinkage is ≥60%, the elongation is ≥20%, the -20°C impact absorption energy is ≥200J, and the -40°C impact absorption capacity is ≥120J; the shear strength of the composite steel plate is ≥280MPa.
[0024] In the composite steel plate substrate composition design of the present invention:
[0025] C: C is an important strengthening element. In order to make the carbon steel plate have appropriate strength, it is necessary to control the mass percentage of C in the steel to be greater than or equal to 0.01%. At the same time, in order to improve the welding performance of the base carbon steel material, it is necessary to control the upper limit of the content of C in the carbon steel. In addition, if the carbon content in the carbon steel base material is high, due to the difference in the carbon concentration gradient of the two materials, a large-scale carbon migration will occur at the interface between the base material and the stainless steel composite material, causing intergranular corrosion of the stainless steel, so the upper limit is controlled to 0.10%. Accordingly, based on this, the present invention controls the C content to 0.01% to 0.10%.
[0026] Si: Similar to carbon, Si is also a commonly used strengthening element in low alloy steel. Adding a certain amount of Si to steel can improve the strength of steel. At the same time, Si is also a weak deoxidizer. During the smelting process, it can play an auxiliary deoxidation role. Most of the SiO2 products formed after deoxidation enter the steel slag and are removed, which will not affect the performance of the steel. In addition, adding a certain amount of Si to steel can reduce the solubility of carbon in austenite, thereby promoting carbon precipitation, promoting the formation of MC precipitation phase, fixing carbon in steel, and preventing large-scale diffusion of carbon. Therefore, a certain amount of Si needs to be added to the steel. However, excessive Si will reduce the welding performance of steel. Because Si has a stronger ability to bind oxygen than iron, it is easy to generate low-melting silicates during welding, increase the fluidity of slag and molten metal, cause splashing, and affect the quality of the welded joint. Therefore, controlling the content of Si within a certain range is helpful to improve the welding forming performance of steel. Therefore, the present invention controls the Si content to 0.2% to 0.7%.
[0027] Mn: Mn is also an important strengthening element, which can effectively improve the strength of the base steel plate. At the same time, the Mn element is an effective austenite stabilizing element. Adding a certain amount of Mn elements can increase the hardenability of steel. Therefore, in order to ensure the strength of steel, the lower limit of Mn is 0.30%. However, the Mn element is very easy to produce center segregation in steel. Excessive addition of Mn elements will cause serious segregation at the center of the thickness of the steel plate and reduce the low-temperature toughness of the core of the steel plate. Therefore, the upper limit of the Mn content is limited to 1.70%. Based on this, the present invention controls the Mn content to 0.30% to 1.7%.
[0028] Ti: Ti is not only a deoxidizing element, but also a strong carbide-forming element and nitride-forming element. In the present invention, adding an appropriate amount of Ti element can, on the one hand, form a stable MC precipitation phase in the steel, fix the carbon element in the substrate, and prevent it from diffusing to the interface of the composite material. At the same time, part of the Ti element participates in fixing the free N element in the steel to form a TiN precipitation phase, which can prevent the growth of austenite grains and refine the grains, thereby improving the strength and toughness of the steel plate at the same time. After Ti fixes part of the free nitrogen element, it helps to ensure that the B element in the steel exists in the steel in a free state, thereby improving the hardenability of the steel. In addition, after Ti deoxidation, Ti2O3 particles can be formed to promote the formation of intracrystalline ferrite and improve the low-temperature impact toughness of the steel. However, when the Ti content in the steel is too high, the size of the TiN and Ti2O3 particles formed becomes larger, so that they no longer have the ability to hinder the growth of austenite and form intracrystalline ferrite. Instead, they will easily become the source of crack initiation and reduce the low-temperature impact toughness of the steel, so the upper limit of Ti is 0.012%. Based on this, the present invention controls the Ti content to 0.006% to 0.012%.
[0029] Als: Al is first of all an important deoxidizing element, which will form aluminum oxide inclusions. Moreover, the Al element can combine with the N element in the steel to form an AlN precipitation phase, which reduces the content of free N elements in the steel, thereby avoiding the combination of the B element in the steel with the N element, promoting the increase of the free B element content in the steel, improving the hardenability of the steel, and helping to improve the strength performance of the steel plate. However, when the acid-soluble aluminum content in the steel is too high, the size of its deoxidation product aluminum oxide will become larger, and because the aluminum oxide inclusions have a strong adsorption capacity, it will lead to the formation of large-sized aluminum oxide clusters, which will clog the water inlet during the steelmaking process and affect the casting process of the molten steel. If these large-sized clustered inclusions enter the steel plate, it will cause the inclusion rating and flaw detection of the steel plate to fail. Therefore, the present invention controls the acid-soluble Als content to 0.008% to 0.018%.
[0030] Nb: Nb is a strong carbide-forming element. Nb can combine with carbon in steel to form MC precipitation phase, stabilize carbon in steel, and prevent carbon from diffusing to the interface. At the same time, adding an appropriate amount of Nb can increase the recrystallization temperature of steel. After the steel is recrystallized and rolled in the austenite region, the austenite grains will not grow rapidly, and the strength and toughness of fine-grained steel are higher. However, when the Nb content in the steel is too high, the size of the MC precipitation phase formed will be larger, which will reduce the toughness of the steel plate and deteriorate the toughness of the heat-affected zone of the weld. Therefore, the present invention controls the Nb content to 0.0090% to 0.050%.
[0031] B: Adding an appropriate amount of B element is to compensate for the decrease in the strength performance of the steel plate due to the reduction of the content of solid-solubilized carbon in the steel after the carbon element in the steel is fixed by stable carbides. If the B element in the steel exists in a free state, some of the B will preferentially occupy the grain boundary position and improve the hardenability of the steel plate. Therefore, the premise for the B element to play a role is that B must exist in the steel in a free state. Therefore, in order to prevent B in the steel from combining with oxygen and nitrogen to form boron oxide and boron nitride, the oxygen content and nitrogen content in the steel must be controlled, which is also the key point of alloy composition design. However, it should be noted that if excessive B is added to the steel, too much B is prone to form a large amount of segregation at the grain boundary, which will be detrimental to the toughness of the steel. Therefore, the present invention controls the B content to 0.0010%≤B≤0.0050%.
[0032] N: A proper amount of Ti and Al elements are added. These two elements can form TiN and AlN precipitation phases with the N element in the steel. When these precipitation phases are fine and dispersed, they can refine the austenite grains, thereby improving the strength and toughness of the steel plate. However, when the N content in the steel is too high, the excess N element will combine with the B element in the steel to generate BN, consume the free B element in the steel, and reduce the effect of the B element on improving the strength of the steel plate. At the same time, too much N element will have an adverse effect on the toughness of the steel, especially when the solid solution N content exceeds 0.005%, the low-temperature toughness of the steel plate will be significantly reduced. Therefore, the present invention controls the N content to 0.0015≤N≤0.0050%.
[0033] Preferably, the composite steel plate substrate of the present invention further contains at least one of the following chemical elements: 0<Ca≤0.0055%, 0<Ni≤0.65%, 0<Cu≤0.55%.
[0034] Ca: Ca is a strong deoxidizing element. Adding an appropriate amount of calcium can control the oxygen content in the steel, thereby preventing the oxidation of the B element. However, when the Ca content in the steel exceeds 0.0055%, large inclusions of calcium oxide and calcium sulfide are easily formed in the steel, which is detrimental to the toughness of the steel. Therefore, the present invention controls the Ca content to 0<Ca≤0.0055%.
[0035] Ni: Ni is a typical austenite stabilizing element, which can significantly improve the hardenability of the steel plate, and can also improve the low temperature toughness of the steel plate. However, the price of Ni is relatively high. Considering the production cost of steel, it is not appropriate to add excessive Ni to the steel. Therefore, the present invention controls the Ni content to 0<Ni≤0.65%.
[0036] Cu: Adding an appropriate amount of Cu element helps to improve the strength of steel and improve the corrosion resistance of steel. However, when the Cu content added to the steel is too high, the steel plate is prone to high-temperature brittleness at high temperatures. Therefore, the present invention controls the Cu content to 0<Cu≤0.55%.
[0037] It should be noted that the addition of the above-mentioned Ca, Ni and Cu elements will increase the production cost of the material. Taking into account the performance and cost control, in the technical solution of the present invention, at least one of the above-mentioned elements can be preferably added.
[0038] Inevitable impurities exist in the composite steel plate substrate of the present invention, P≤0.017%, S≤0.020%, O≤0.0050%.
[0039] P, S and O are all impurity elements in steel. When technical conditions permit, in order to obtain steel with better performance and higher quality, the content of impurity elements in steel should be reduced as much as possible.
[0040] P: P is a harmful element for most steel plates. The main reason is that P is very easy to segregate to the grain boundary, reducing the bonding force between atoms at the grain boundary, causing the temper brittleness of the steel plate, especially when the steel plate is working at high temperature, the temper brittleness of P will be aggravated. Therefore, the P content is controlled to P≤0.017% in the present invention.
[0041] S: The S element in steel is very easy to combine with the Mn element in steel to form MnS inclusions. The higher the S content, the larger the size of the MnS formed, which is not good for the strength and toughness of the steel plate. At the same time, when the S content is too high, it will cause the center segregation of the slab and easily cause hot cracks. Therefore, the present invention controls the S content to S≤0.020%.
[0042] O: The oxygen element in steel basically exists in the form of oxides. When the O element content in steel is too high, it means that there are too many oxides in the steel, and large inclusions may exist, which affects the strength and toughness of the steel plate. Therefore, the present invention controls the O content to O≤0.0050%.
[0043] The surface microstructure of the composite steel plate substrate of the present invention is 60-80% ferrite + 20-40% pearlite, and the central microstructure of the substrate is 30-40% pearlite + 60-70% ferrite. Since the working condition of the composite steel plate involved in the present invention is a maximum working temperature of 300°C, the structure type of the composite steel plate substrate is controlled to be ferrite + pearlite, so as to meet the strength and toughness performance required by its working condition. The pearlite content in the surface microstructure of the substrate is controlled to be 20-40%, which is slightly lower than the proportion of 30-40% in the central microstructure. The purpose is to reduce the pearlite content in the surface microstructure on the basis of ensuring the basic mechanical properties of the material, so as to reduce the concentration of carbon elements at the surface, thereby reducing the carbon element concentration difference of the materials on both sides of the transition layer, and weakening the concentration barrier of carbon elements on the substrate surface to migrate to the transition layer.
[0044] The rolled composite steel plate substrate of the present invention has a stable MC precipitation phase, wherein M represents one or two of Nb and Ti, and the average major axis length of the MC precipitation phase is less than 600nm. When the major axis length of the precipitation phase is large, it is easy to form a crack source for microcrack initiation inside the steel plate, thereby adversely affecting the mechanical properties of the steel plate, so it is necessary to control the average major axis length of the MC in the substrate to be less than 600nm. In the substrate of the rolled composite steel plate of the present invention, a carbide precipitation phase with a smaller size is formed as much as possible to ensure that while the carbon fixation effect of the carbide is fully exerted, the mechanical properties of the steel plate will not be adversely affected by the precipitation of the carbide, so the number ratio of the MC precipitation phase with a major axis length less than 600nm to all MC precipitation phases is limited to be greater than 50%.
[0045] The volume density of the MC precipitated phase with a major axis size of less than 600 nm in the substrate of the present invention is greater than 2.0×104 Pieces / mm 3 In order to prevent the free carbon element from diffusing into the composite material, the MC precipitate phase is formed in the steel through the composition and process control to fix the free carbon element in the steel. Therefore, in the present invention, it is necessary to ensure that the volume density of the MC precipitate phase with a major axis size of less than 600nm is greater than 2.0×10 4 Pieces / mm 3 Only by doing so can we effectively control the carbon element in the steel and avoid the large-scale diffusion of free carbon elements to the stainless steel side.
[0046] The composite steel plate composite material of the present invention has a stable MC precipitation phase, wherein M represents one or more of Cr, Mo, Nb, and Ti, and the average major axis length of the MC precipitation phase is less than 700nm. The larger the size of the carbide in the composite material, the greater the impact on the corrosion resistance of the stainless steel. Therefore, it is hoped that the size of the carbide precipitation phase in the composite material is as small as possible. However, in the production process of the composite material and the rolled composite steel plate, some carbide precipitation phases will inevitably be generated. In order to ensure the corrosion resistance of the rolled composite steel plate, the present invention requires that the average major axis length of the MC precipitation phase in the composite material is less than 700nm.
[0047] The volume density of the MC precipitated phase in the composite material of the present invention is less than 1.0×10 4 Pieces / mm 3 From the perspective of controlling the amount of carbide precipitation phase in the composite material, it is hoped that the amount of carbides is as small as possible, that is, the smaller the volume density is, the better. However, some carbides will inevitably form during the heat treatment of the composite steel plate. The volume density of carbides is controlled to be less than 1.0×10 4 Pieces / mm 3 It can ensure the excellent corrosion resistance of the composite material.
[0048] In the composite material of the present invention, the MC precipitate phase with a major axis length less than 700nm accounts for more than 50% of the total MC precipitate phase. In the present invention, the "volume density" of the MC precipitate phase is measured according to the method described in the YB / T 5320-2006 standard. In order to reduce the carbide precipitate phase in the composite material as much as possible to increase the corrosion resistance of the composite material, the size and number of the MC precipitate phase are limited in the present invention, that is, the MC precipitate phase with a major axis length less than 700nm accounts for more than 50% of the total MC precipitate phase. When the number and size of the carbide precipitate phase exceed the limit range, the corrosion resistance of the composite material will be greatly reduced, affecting the safe service performance of the rolled composite steel plate.
[0049] The composite layer of the present invention is stainless steel (including austenitic stainless steel, ferritic stainless steel, duplex stainless steel, super stainless steel, etc.), and the σ phase in its microstructure is a metal phase with high hardness and low plasticity. When it exists in stainless steel, especially when it precipitates along the grain boundary, it will have a great impact on the plasticity of the steel, resulting in a significant reduction in the impact toughness of the steel. Therefore, the σ phase ratio of stainless steel is ≤1.5%, especially the σ phase ratio near the bonding interface (transition layer) is ≤0.5%.
[0050] The present invention also provides a method for manufacturing the corrosion-resistant rolled composite steel plate, which comprises the following steps:
[0051] 1) Smelting and casting to obtain base material and composite casting billet
[0052] The base material ingot is obtained by smelting and casting according to the above composition; during the smelting process, deoxidizers Mn+Si, Al, and Ti alloys are sequentially added to the molten steel for deoxidation, and Mn+Si and Al are sequentially added for pre-deoxidation. After pre-deoxidation, the oxygen level of the molten steel is 0.0020% to 0.0075%, and then Ti is added for final deoxidation; after deoxidation, B element is added; after casting, a carbon steel base material ingot is obtained; at the same time, a stainless steel composite ingot is obtained;
[0053] 2) Assembly
[0054] After surface treatment of the substrate ingot and the composite ingot, the ingot is overlapped, the overlapped ingot is sealed by welding around, vacuumized, and sealed again to form a composite slab; preferably, the vacuum degree after vacuuming is 8-60Pa;
[0055] 3) Composite slab rolling
[0056] The composite slab is heated to 1020-1200°C, and then rolled in two stages, the total reduction rate of the composite slab in the first stage is not less than 60%, the total reduction rate in the second stage is not less than 20%, the reduction rate of the last pass is 10-18%, the total reduction rate of the two-stage rolling is not less than 80%, and the final rolling temperature is above 850°C;
[0057] 4) Heat treatment: quenching and tempering the composite steel plate.
[0058] Preferably, in step 2), the surfaces of the substrate and the composite ingot are surface treated to ensure that there are no obvious oil stains, slag inclusions, cracks or other surface defects on the ingot surface, and the roughness of the processed surface of the ingot is not greater than 2.0 Ra.
[0059] Preferably, in step 4), the quenching temperature is 920-955°C, the quenching holding time is T1=(1-1.2)H, and after the holding is completed, the steel plate is taken out of the furnace and cooled to room temperature with water, wherein T1 is in min, and H is the thickness of the steel plate in mm.
[0060] Preferably, in step 4), the tempering temperature is 550-700° C., and the tempering holding time T2=(1-1.5)H, wherein T2 is in min, and H is the thickness of the steel plate in mm.
[0061] In the manufacturing method of the present invention,
[0062] A large amount of uniformly dispersed nano-scale MC precipitation phases need to be generated in the composite steel plate substrate of the present invention, and the MC precipitation phase is used to fix the free carbon element in the carbon steel substrate to prevent the carbon element from diffusing in large quantities to the interface between the substrate and the composite material, thereby causing the stainless steel to form carbides and reduce its corrosion resistance, thereby improving the service safety performance of the rolled composite steel plate for high-temperature equipment. However, the free carbon in the steel is a major strengthening element of the carbon steel substrate. When most of the free carbon elements are fixed in the form of MC, the strength of the carbon steel will decrease. In order to compensate for the strength loss after the carbon elements are fixed. It is necessary to add the B element to improve the hardenability of the steel plate. The hardenability of the B element mainly works through the distribution of free B at the grain boundary. Since the B element is an extremely active element, on the one hand, it can combine with the oxygen element in the molten steel to form boron oxide; on the other hand, the boron element is also easy to combine with the N element to form boron carbide.
[0063] For this purpose, the deoxidation sequence of molten steel and the timing of adding B element are specially designed in the technical solution of the present invention. That is, during deoxidation, Si+Mn is used for pre-deoxidation first, and most of silicon oxide and manganese oxide will float to the top slag. Using strong deoxidizer Al for deoxidation can more accurately control the oxygen level (determined according to the method for measuring oxygen content in molten steel recorded in ISO 14284:1996 standard) between 0.0020% and 0.0075%, and then Ti is used for final deoxidation to form a large amount of Ti oxide, and the added Ti can combine with the free nitrogen element in the steel to form TiN. That is, the addition of Ti element will further reduce the free oxygen concentration in the steel. Within a certain oxygen position range (0.0020% to 0.0075%), the size of the Ti2O3 inclusions formed after deoxidation is appropriate (2-5μm), which is conducive to the formation of part of the acicular ferrite structure during solidification and subsequent phase transformation, and improves the toughness of the steel plate. In addition, Ti element can also combine with N element in steel to generate part of TiN, which can reduce the adverse effect of solid solution nitrogen on the toughness of steel on the one hand, and on the other hand, TiN can precipitate at high temperature during solidification, play a role in pinning the growth of austenite, and refine the original austenite grains. When the oxygen and titanium elements in the steel are controlled in place, an appropriate amount of B element is added, thereby ensuring that the added B element is mainly present in the steel in a free state, ensuring that the base steel plate has a high hardenability, and can significantly improve the strength of the steel plate.
[0064] In step 2), the surfaces of the substrate and the composite ingot are processed to ensure that there are no obvious surface defects such as oil stains, slag inclusions, cracks, etc. on the surface of the ingot, and at the same time, the roughness of the processed surface of the ingot is required to be no greater than 2.0Ra. After the vacuum is evacuated, the vacuum degree is 8-60Pa, thereby ensuring the rolling effect of the composite slab.
[0065] In step 3), the composite slab is heated to 1020 to 1200°C for rolling because: when the heating temperature is less than 1020°C, the carbides and nitrides in the base material ingot cannot be completely dissolved, which will reduce the pinning effect of the carbides on the austenite grains during the rolling process; at the same time, within this temperature range, it is conducive to the homogenization of the austenite of the composite material, and the carbides in the composite material are also completely dissolved. When the heating temperature of the ingot is higher than 1200°C, it is easy to cause the rapid growth of the austenite grains of the base material and the composite material, which will damage the mechanical properties of the steel.
[0066] Accordingly, it is preferred that the total reduction rate of the slab in the first stage rolling is not less than 60%, the total reduction rate in the second stage rolling is not less than 20%, the reduction rate of the last pass is 8-18%, the total cumulative reduction rate of the two-stage rolling is not less than 80%, and the final rolling temperature is above 850°C.
[0067] Through the first stage of high-temperature and high-reduction rolling, the material can be fully recrystallized during the rolling deformation process, the austenite grains can be continuously refined, and the formation of larger austenite grains in the steel can be inhibited, thereby improving the low-temperature toughness of the steel. When the total reduction rate in the first stage is less than 60%, the austenite grain size in the steel is larger, which is not conducive to the strength and toughness indicators of the steel plate.
[0068] The total reduction rate of the second stage rolling is not less than 20%, which can further promote the refinement of austenite grains. The final rolling pass reduction rate is 8-18%, which can increase the dislocation density in the steel and ensure the strength of the steel plate. When the reduction rate is lower than 8%, the dislocation density is low, which is not conducive to strength improvement. When the reduction rate is higher than 18%, the rolling torque is too large, which is not conducive to the rolling equipment. When the final rolling temperature is lower than 850℃, the deformation resistance of the steel plate increases, and it is difficult to ensure a larger final rolling reduction rate.
[0069] In step 4), the quenching temperature is 920-955°C, the quenching holding time is T1=(1-1.2)H, and after the holding is completed, the steel is taken out of the furnace and water-cooled to room temperature, wherein T1 is in min, and H is the thickness of the steel plate in mm.
[0070] It should be noted that during the quenching process, when the quenching temperature is lower than 920°C, the homogenization of the austenite of the steel takes a long time, which will reduce the efficiency of the heat treatment; and if the quenching temperature of the steel is higher than 955°C, part of the austenite in the carbon steel tends to grow and is easy to form a mixed crystal structure, which is not conducive to the uniformity of the steel structure. Accordingly, when the quenching and holding time T1 of the steel is less than 1H, it cannot be fully austenitized, and when the quenching and holding time T1 of the steel exceeds 1.2H, it will exceed the time required for the austenitization of the steel, which will reduce the efficiency of the quenching process.
[0071] In step 4), the tempering temperature is 550-700°C, and the tempering holding time T2=(1-1.5)H, wherein T2 is in min, and H is the thickness of the steel plate in mm.
[0072] Step 4) During the tempering process, when the tempering temperature of the steel is lower than 550°C, a longer tempering time is required to remove the residual quenching stress in the steel, which will reduce the tempering efficiency and the MC precipitation phase in the carbon steel will form slowly; and when the tempering temperature of the steel is higher than 700°C, the MC precipitation phase in the steel is prone to Ostwald coarsening and aggregation and growth, which is not conducive to the formation of fine and dispersed MC precipitation phases in the steel. Accordingly, when the tempering holding time T2 is lower than 1.0H, the quenching stress of the steel tends not to be completely removed, and when the tempering holding time T2 is higher than 1.5H, the MC precipitation phase in the steel is prone to coarsening and will reduce the production efficiency of the tempering process.
[0073] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0074] 1. The present invention forms fine and dispersed spherical (2-5 μm) Ti2O3 oxides in steel as nucleation cores for MC carbide precipitation phases. Combined with the design of alloy composition optimization and heat treatment process design, a large number of dispersed and distributed nano-scale MC (M represents one or more of Nb and Ti) precipitation phases can be formed in the substrate, which can fix the free carbon element in the substrate, reduce the diffusion and aggregation of carbon elements to the composite interface, reduce the precipitation of stainless steel grain boundary carbides, and ensure the corrosion resistance of the composite rolled steel plate. In particular, when the rolled composite steel plate is used in high-temperature equipment, even under 300°C high-temperature working conditions, the high-melting-point Ti2O3 oxide (melting point of 2130°C) formed by controlling the smelting process can still stably exist in the steel and continue to play a role as the precipitation core of MC carbides. That is, some of the free carbon elements in the steel can still react with the alloy elements in the steel with Ti2O3 oxide as the nucleation core to form fine MC carbides, thereby further fixing the carbon elements, ensuring that the carbon elements in the carbon steel do not diffuse to the interface, and protecting the corrosion resistance of the rolled composite steel plate under long-term high-temperature service.
[0075] 2. In the existing production process of low-alloy high-strength steel, aluminum is often used as a deoxidizer to reduce the oxygen content in the steel as much as possible. The advantage of aluminum deoxidation is its high deoxidation efficiency. Its disadvantage is that after aluminum deoxidation, the Al2O3 inclusions formed in the molten steel are likely to have an adverse effect on the flaw detection and performance of the steel plate. This is mainly because single Al2O3 inclusions are mostly irregular and sharp, which are easy to form crack sources inside the material during the stress process of the substrate; at the same time, Al2O3 inclusions are very easy to aggregate and grow in the molten steel, forming large-sized Al2O3 inclusion clusters and blocking the pouring nozzle. Moreover, when large-sized inclusions exist in the steel, the tensile and impact properties of the steel plate are very likely to fluctuate. In addition, Al2O3 inclusions cannot serve as the nucleation core of the carbide precipitation phase.
[0076] In the present invention, by controlling the type of deoxidizer, the order of deoxidation and the amount of deoxidizer added during the steel smelting process, a spherical (2-5 μm) Ti2O3 oxide with a high melting point and fine dispersion distribution is finally formed in the steel. Ti2O3 oxide is not easy to aggregate and grow in the molten steel, has no edges and corners, has no obvious damage to the flaw detection and mechanical properties of the steel plate, and can optimize the organization type of the steel plate; by controlling the element content ratio, TiN precipitation is controlled, and the austenite grains are refined; by designing the order of adding steel alloys, the oxidation and nitridation of the B element can be effectively reduced, so as to make full use of the added B element, maximize the hardenability of the steel plate, refine the grains, and ensure that the steel plate has high strength and excellent low-temperature toughness.
[0077] In addition, through the control of the smelting process, especially through the control of the type of deoxidizer, the deoxidation sequence and the amount of deoxidizer added, the fine and dispersed spherical (2-5μm) Ti2O3 oxide formed in the steel can serve as the nucleation core of the MC carbide precipitation phase. Combined with the design of the alloy composition optimization and the design of the heat treatment process, a large number of dispersed and distributed nano-scale MC (M represents one or more of Nb and Ti) precipitation phases can be formed in the substrate, which can fix the free carbon element in the substrate, reduce the diffusion and aggregation of carbon elements to the composite interface, reduce the precipitation of stainless steel grain boundary carbides, and ensure the corrosion resistance of the composite rolled steel plate. In particular, when the rolled composite steel plate is used for high-temperature equipment, even under the high-temperature working condition of 300°C, the high-melting-point Ti2O3 oxide (melting point is 2130°C) formed by controlling the smelting process can still stably exist in the steel and continue to play a role as the precipitation core of MC carbides. That is, some of the free carbon elements in the steel can still react with the alloy elements in the steel with Ti2O3 oxide as the nucleation core to form fine MC carbides, thereby further fixing the carbon elements, ensuring that the carbon elements in the carbon steel do not diffuse to the interface, and protecting the corrosion resistance of the rolled composite steel plate under long-term high-temperature service.
[0078] The composite steel plate produced by the present invention has excellent corrosion resistance and can be effectively used in the energy and chemical industry as a manufacturing material for reaction vessels at room temperature to 300° C. It has very important practical significance and a very broad application prospect. DETAILED DESCRIPTION
[0079] The rolled composite steel plate for high temperature equipment and the manufacturing method thereof according to the present invention will be further explained and illustrated below in conjunction with specific embodiments. However, such explanation and illustration do not constitute an improper limitation on the technical solution of the present invention.
[0080] The compositions of the substrate and the composite layer of the rolled composite steel plate of the embodiment and the comparative example of the present invention are shown in Table 1, and the remainder includes Fe and other inevitable impurities. The composite layer materials of the rolled composite steel plate in the embodiment and the comparative example are all illustrated by austenitic stainless steel. The manufacturing process parameters of the embodiment of the present invention are shown in Table 2.
[0081] The manufacturing method of the embodiment of the present invention comprises the following steps:
[0082] 1) Smelting and casting: Smelting and continuous casting are carried out according to the chemical composition shown in Table 1 to obtain a casting billet. The smelting equipment adopts a 500Kg vacuum induction furnace. First, 410kg of industrial pure iron is added to the vacuum induction furnace. According to the alloy composition ratio of the steel, a certain amount of CaO is added with the furnace (the added CaO is used for slag making during smelting); vacuum is drawn, and smelting is carried out at a vacuum degree of about 25Pa at the lowest. Argon gas needs to be filled for atmosphere protection during the smelting process; after the pure iron is melted, deoxidizers Si+Mn and Al are added in sequence for pre-deoxidation, and according to the online monitoring results of the molten steel composition, the amount of deoxidizer added is finely adjusted and the oxygen level of free oxygen in the molten steel is controlled to be 0.0020-0.0075%, and then an appropriate amount of Ti is added for final deoxidation; alloys such as Nb are added for alloying treatment, and finally B is added, and the ingot is cast by the top injection method;
[0083] 2) Assembly: Process the surfaces of the base carbon steel slab and the composite stainless steel slab. The roughness of the butt surface of the two materials is ≤2.0Ra. After surface inspection, ensure that there are no surface defects such as oil stains, slag inclusions, cracks, etc. After welding around the slab, vacuum is drawn with a vacuum degree of 8 to 60Pa.
[0084] 3) rolling, heating the composite slab at 1020-1200° C., and then performing two-stage rolling, the total cumulative rolling reduction rate is not less than 80%, and the final rolling temperature is above 850° C.;
[0085] 4) Heat treatment, quenching and tempering the rolled composite steel plate; quenching the composite rolled steel plate, the quenching temperature is 920-955°C, the quenching holding time is T1=(1-1.2)H, after the holding is completed, it is taken out of the furnace and water-cooled to room temperature; then tempering is performed, the tempering temperature is 550-700°C, the tempering holding time is T2=(1-1.5)H, and air-cooling is performed after taking out of the furnace; wherein, T1 and T2 are in min, and H is the thickness of the steel plate in mm.
[0086] In the present invention, the chemical composition design and related processes of the composite steel plates of Examples 1 to 7 all meet the design specification requirements of the present invention.
[0087] Accordingly, the composite steel plates of Comparative Examples 1 to 5 are manufactured using the same process steps as Examples 1 to 7, except that: the alloy element content of the base carbon steel of Comparative Examples 1 to 4 exceeds the design range, and the element content of Comparative Example 5 is within the design range, but in the smelting and casting operations of the above step 1), the order of adding deoxidizer and B alloy in Comparative Examples 1 to 5 is different; the heat treatment tempering process is different.
[0088] Electrolytic samples were taken from the base material and the composite stainless steel side of the respective bonding interface of the composite steel plates of Examples 1 to 7 and the control composite steel plates of Comparative Examples 1 to 5. The MC precipitate phase in the stainless steel was extracted by electrolytic extraction, and the precipitate phases of different scale ranges were separated by filter membranes of different particle sizes; the particle size distribution of the precipitate phase was detected by a laser particle size analyzer, and the number and size distribution range of the MC precipitate phase (M represents one or more of Nb, Ti, Cr, and Mo) in the steel plates of each embodiment and comparative example were finally confirmed by using image analysis software, and the data obtained by observation and analysis were finally listed in Table 3 (base material) and Table 4 (composite material at the bonding interface, i.e., transition layer).
[0089] As can be seen from Table 3, the total number of precipitated phases in the composite steel plate substrate materials of Examples 1 to 7 ranges from 516 to 594, which is much higher than 297 to 319 in the substrate materials of Comparative Examples 1-5, indicating that after the implementation of the technical solution of the present invention, a larger number of MC carbide precipitation phases can be formed in the substrate material, thereby ensuring the effect of fixing free carbon in carbon steel by using stable carbides in the substrate as designed in the technical solution; moreover, the size of the MC precipitation phases in the composite steel plate substrate materials of Examples 1 to 7 is relatively small, and their main distribution range is 300 to 600 nm, the average major axis length of the MC precipitation phase is less than 600 nm, and the volume density of the MC precipitation phase is greater than 2.0×10 4 Pieces / mm 3. The number ratio of MC precipitates with a size less than 600nm to all MC precipitates is greater than 50%. When the size of the precipitates is small, it can play a role in pinning the growth of austenite grains to a certain extent, thereby refining the grains and further improving the strength and toughness of the material. In contrast, the size of the MC precipitates in the carbon steel of the rolled composite steel plate substrate in Comparative Examples 1 to 5 is relatively large, the average major axis length of the MC precipitates is greater than 800nm, the size distribution range of the main precipitates is above 800nm, and the proportion of precipitates above 1000nm is relatively high, which has a poor pinning effect on austenite grains, resulting in a larger grain size and affecting the strength and toughness of the steel plate. Due to the small number of stable precipitates formed in the carbon steel material of the comparative example, the amount of free carbon fixed by the precipitates in the carbon steel is reduced, resulting in a large amount of free carbon being segregated to the bonding interface, thereby generating a large amount of carbides precipitated from grain boundaries at the composite material at the bonding interface, reducing the corrosion resistance of the composite material at the bonding interface.
[0090] As shown in Table 4, in the composite steel plate cladding materials of Examples 1 to 7, the number of MC precipitates detected is 182 to 244, which is much less than 424 to 506 in the comparative example, and the volume density of the MC precipitates in the cladding material at the transition layer of the embodiment is less than 1×10 4 Pieces / mm 3 . This shows that the amount of carbon in the base carbon steel material of Examples 1 to 7 that diffuses into the composite material through the bonding interface (transition layer) is small, and the amount of MC formed is small, while in Comparative Examples 1 to 5, a large amount of carbon in the carbon steel material diffuses into the composite material through the bonding interface, resulting in a large amount of carbides in the corresponding composite material. At the same time, it can be seen from Table 4 that in the composite material at the bonding interface of Examples 1 to 7, the average major axis length of the MC precipitation phase is less than 700nm, and the MC precipitation phase with a size less than 700nm accounts for more than 50% of the total MC precipitation phase; correspondingly, the average size of the MC precipitation phase obtained in the comparative example is greater than 850nm. This also further illustrates that the fixing effect of carbides on free carbon in the examples is much better than that in the comparative example.
[0091] After analyzing the carbide precipitation phases of the composite steel plates of Examples 1 to 7 and the comparative steel plates of Comparative Examples 1 to 5, the mechanical properties and corrosion resistance of the steel plates of Examples 1 to 7 and Comparative Examples 1 to 5 were also evaluated. The evaluation results are shown in Table 5. As can be seen from Table 5, the yield strength and tensile strength of the carbon steel substrate of the comparative example are lower than those of the embodiment. The main reason is that the smelting process, alloy addition sequence and heat treatment process of the carbon steel of the comparative example substrate are different from those of the embodiment, thereby causing the hardenability of the B element in the comparative steel to not fully play its role, and the precipitation phases in the steel are different, which has different effects on the microstructure of the steel plate. In the composite steel plate substrate of the present invention, the surface microstructure is 60-80% ferrite (F) and 20-40% pearlite (P), and the central microstructure of the substrate is 30-40% pearlite and 60-70% ferrite. The smaller precipitation phases in the embodiment further refine the austenite grains, which plays a certain role in improving the strength and toughness of the steel plate.
[0092] The stainless steel at the interface of the rolled composite steel plates of the embodiment and the comparative example was subjected to an intergranular corrosion test according to ASTM A262 practice E method. The test results are shown in Table 6. From the results, it can be seen that the stainless steel at the interface of the rolled composite steel plate prepared according to the technical requirements of the present invention has excellent corrosion resistance. Therefore, among the composite steel plates of the embodiments 1 to 7, the corrosion resistance of the composite stainless steel plates of each embodiment is far superior to that of the comparative example.
[0093] In summary, the composite steel plate of the present invention can generate a large number of dispersedly distributed nano-scale MC (M represents one or two of Nb and Ti) precipitation phases in the steel by optimizing the design and production process, controlling the type of deoxidizer, deoxidation order and the amount of deoxidizer added in the steel smelting process, and performing alloying treatment in a certain order, in conjunction with a specific production process. These nano-scale MC precipitation phases can fix the free carbon elements in the base carbon steel, thereby preventing these carbon elements from diffusing in large quantities to the bonding interface, causing the stainless steel to form a large number of carbide precipitation phases, resulting in a decrease in the corrosion resistance of the stainless steel. Therefore, the use of the technical solution of the present invention can ensure the strength and toughness of the carbon steel substrate, and at the same time can greatly improve the corrosion resistance of the rolled composite steel plate, and ensure the safety performance of the rolled composite steel plate when it is in high temperature and long-term service.
[0094] In addition, it should be noted that the combination of the various technical features in the present invention is not limited to the combination described in the claims of the present invention or the combination described in the specific embodiments, and all technical features described in the present invention can be freely combined or combined in any way unless there is a contradiction between them.
[0095] It should also be noted that the above-listed embodiments are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and similar changes or modifications made therewith can be directly derived or easily associated with the contents disclosed by those skilled in the art from the present invention, and all should belong to the protection scope of the present invention.
[0096]
[0097]
[0098]
[0099]
[0100]
[0101]
[0102]
Claims
1. A corrosion-resistant rolled composite steel plate, comprising a substrate, a composite layer and a transition layer between the substrate and the composite layer, wherein: The weight percentage of the components of the substrate is: C: 0.01% to 0.10%, Si: 0.2% to 0.7%, Mn: 0.30% to 1.70%, Ti: 0.006% to 0.012%, Als: 0.008% to 0.018%, Nb: 0.0090% to 0.050%, B: 0.0010% to 0.0050%, N: 0.0015% to 0.0050%, P≤0.017%, S≤0.020%, O≤0.0050%, and the balance includes Fe and other inevitable impurities; The surface microstructure of the composite steel plate substrate is 60-80% ferrite + 20-40% pearlite + MC precipitation phase, and the central microstructure of the substrate is 30-40% pearlite + 60-70% ferrite + MC precipitation phase; wherein M represents one or two of Nb and Ti, the average major axis length of the MC precipitation phase is less than 600nm, and the volume density of the MC precipitation phase with a major axis length less than 600nm is greater than 2.0×10 4 Pieces / mm 3 ; The composite steel plate is made of stainless steel, and its microstructure contains MC precipitated phase, wherein M represents one or more of Cr, Mo, Nb, and Ti, the average major axis length of the MC precipitated phase is less than 700 nm, and the volume density of the MC precipitated phase is less than 1.0×10 4 Pieces / mm 3 ; Preferably, the stainless steel is austenitic stainless steel, ferritic stainless steel, duplex stainless steel or super stainless steel.
2. The corrosion-resistant rolled composite steel plate according to claim 1, characterized in that: The balance of the composite steel plate base material is Fe and other inevitable impurities.
3. The corrosion-resistant rolled composite steel plate according to claim 1 or 2, characterized in that: The composite steel plate substrate also contains at least one of the following chemical elements: 0<Ca≤0.0055%, 0<Ni≤0.65%, 0<Cu≤0.55%.
4. The corrosion-resistant rolled composite steel plate according to claim 1, 2 or 3, characterized in that: In the composite steel plate substrate, the MC precipitated phases with a major axis length of less than 600 nm account for more than 50% of the total MC precipitated phases.
5. The corrosion-resistant rolled composite steel plate according to claim 1, 2, 3 or 4, characterized in that: In the composite steel plate layer, the MC precipitated phase with a major axis length less than 700 nm accounts for more than 50% of the total MC precipitated phase.
6. The corrosion-resistant rolled composite steel plate according to claim 1, 2, 3, 4 or 5, characterized in that: There is also a very small amount of σ phase in the microstructure of the composite steel plate layer, and the σ phase ratio is ≤1.5%. Preferably, the σ phase ratio near the transition layer is ≤0.5%.
7. The corrosion-resistant rolled composite steel plate according to claim 1, 2, 3, 4, 5 or 6, characterized in that: The thickness of the composite steel plate substrate is ≥6 mm, the thickness of the composite layer is ≥2 mm, and preferably, the thickness of the transition layer is ≤230 μm.
8. The corrosion-resistant rolled composite steel plate according to claim 1, 2, 3, 4, 5, 6 or 7, characterized in that: The yield strength of the composite steel plate substrate is ≥255MPa, the tensile strength is ≥390MPa, the cross-sectional shrinkage is ≥60%, the elongation is ≥20%, the -20°C impact absorption energy is ≥200J, and the -40°C impact absorption capacity is ≥120J; the substrate grain size grade is not less than grade 6.0; the shear strength of the composite steel plate is ≥280MPa.
9. The method for manufacturing a corrosion-resistant rolled composite steel plate according to any one of claims 1 to 8, wherein: The steps include: 1) Smelting and casting to obtain base material and composite casting billet The base material ingot is obtained by smelting and casting the components according to claim 1, 2 or 3; in the smelting process, Mn+Si and Al are first added in sequence for pre-deoxidation, and the oxygen level of the molten steel after pre-deoxidation is 0.0020% to 0.0075%, and then Ti is added for final deoxidation; after deoxidation, B element is added; after casting, the base material ingot is obtained; at the same time, a stainless steel composite ingot is obtained; 2) Assembly After surface treatment of the substrate ingot and the composite ingot, the ingot is overlapped, the overlapped ingot is sealed by welding around, vacuumized, and sealed again to form a composite slab; preferably, the vacuum degree after vacuuming is 8-60Pa; 3) Composite slab rolling The composite slab is heated to 1020-1200°C, and then rolled in two stages, the total reduction rate of the composite slab in the first stage is not less than 60%, the total reduction rate in the second stage is not less than 20%, the reduction rate of the last pass is 8-18%, the total reduction rate of the two-stage rolling is not less than 80%, and the final rolling temperature is above 850°C; 4) Heat treatment: quenching and tempering the composite steel plate.
10. The method for manufacturing a corrosion-resistant rolled composite steel plate according to claim 9, wherein: In step 2), the surfaces of the substrate and the composite ingot are treated to ensure that there are no obvious oil stains, slag inclusions, cracks or other surface defects on the ingot surface, and the roughness of the ingot surface is not greater than 2.0 Ra.
11. The method for manufacturing a corrosion-resistant rolled composite steel plate according to claim 9, wherein: In step 4), the quenching temperature is 920-955°C, the quenching holding time is T1=(1-1.2)H, and after the holding is completed, the steel is taken out of the furnace and water-cooled to room temperature, wherein T1 is in min, and H is the thickness of the steel plate in mm.
12. The method for manufacturing a corrosion-resistant rolled composite steel plate according to claim 9 or 11, characterized in that: In step 4), the tempering temperature is 550-700° C., and the tempering holding time T2=(1-1.5)H, wherein T2 is in min, and H is the thickness of the steel plate in mm.
Citation Information
Patent Citations
Composite bullet-proof steel plate and production method thereof
CN107310218A
Bullet-proof steel plate with excellent cold-bending workability, and production method thereof
CN107310219A
Method for improving interface of copper-aluminum composite material
CN108231273A
Thick steel plate for low temperature use and capable of being welded in superhigh energy and its production process
CN101045976A
Austenitic stainless steel clad steel plate and process for manufacturing same
CN105658831A